Family law II - Agnes, Flavia (New Delhi : Oxford University Press, 2011)
Vol.2-Marriage, Divorce , and matrimonial litigation
Includes bibliographical references and index.
Keywords: Domestic relations -- India; Women's rights -- India; Constitutional law -- India; Citizenship -- India